Hikmah Kisah Kenabian Sebagai Tatsbit Al-Qalb Nabi Muhammad Saw Dalam Al-Qur’an - Rohimah Rohimah; Kusnadi Kusnadi; Deddy Ilyas (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2022)
The word Tatsbit comes from the word tsabata, which literally means permanent. And the term means determination / firmness. While al-Qalb is taken from the root word, namely Qalbun which means heart. So when combined Tasbit al-Qalb what the researcher means is to strengthen the heart that is leaning on the Prophet Muhammad. There are several factors that cause the tasbit of al-Qalb of the Prophet Muhammad, including the presence of terror, intimidation, persuasion, severity of torture and actions that befall Rasulullah saw, isolation, wounds wrapped in grief. As for the wisdom of prophetic stories in the Al-Qur'an, Allah presents as a soul strengthener or strengthens the heart of the Prophet in his missionary journey to uphold Allah's words. In the stoory of the Prophet Yusuf as. itself, and the meaning of the context can be seen from the relationship of the story of the Prophet Yusuf as. which was revealed to the Prophet Muhammad. by looking at the situation or events that surround the prophetic history of the Prophet Muhammad. While the story of the Prophet Yunus as. it was an inspiration for the Prophet Muhammad when he experienced rejections at the beginning of the Prophet starting his da'wah, and when the angel Gabriel wanted to offer help to the Prophet to punish the Ta'if who had denied and rejected the Prophet, he forbade it. Then Allah SWT also comforted the heart of the Prophet Muhammad on the journey of Isra 'Mi'raj. It was during this spiritual journey that the Prophet Muhammad received the command to pray.